Analytical and numerical assessments of local overpressure from hydrogen gas explosions in petrochemical plants. (25th August 2016) - Bang, Boohyoung; Park, Hyunsu; Kim, Jonghun; Al‐Deyab, Salem S.; Yarin, Alexander L.; Yoon, Sam S.
Summary: Accurate prediction of pressure rise is important for safety assessments of a petrochemical plant in the event of an explosion accident. The sudden pressures arising from gas explosions at various hydrogen concentrations in air have been predicted analytically and numerically. These solutions were compared against experimental data. The analytical solution, based on the self‐similar solution for pointwise strong explosions in an open space, which assumed no energy loss and premixed fuel‐air mixture, reasonably predicted the explosive‐ignition detonation case while the numerical solutions were more suitable to model spark‐ignition deflagration cases that accounted for the effect of turbulence arising from three‐dimensionality and presence of obstacles in the computational domain. Comparison of both analytical and numerical results against experimental data indicates that their differences are within a 30% margin. The analytical model presented herein can be useful for field engineers who want conservative estimates of the overpressure resulting from explosive‐ignition detonation. Copyright © 2016 John Wiley & Sons, Ltd.